Tears of a warrior : a family's story of combat and living with PTSD - Seahorn, Janet J.; Seahorn, E. Anthony (Fort Collins, CO : Team Pursuits, 2008)
The author writes from his experience as a young army officer in Vietnam who served with the Dauntless Black Lions of the 1st Infantry Division. His spouse and co- author describes her perspective as a wife and mother who has lived the past thirty years with a veteran who suffers from the physical, and more specifically, the mental scars of combat. You will become familiar with how PTSD affects the veterans and their families and explore strategies for living with PTSD.
Includes bibliographical references (p. 179-183) and index.
Keywords: Post-traumatic stress disorder -- United States; Vietnam War, 1961-1975 -- Veterans -- Mental health; Vietnam War, 1961-1975 -- Psychological aspects; Veterans -- Mental health -- United States; Soldiers -- Mental health -- United States; War neuroses -- United States -- History; War -- Psychological aspects